Pengaruh Nilai Budaya Terhadap Kinerja UMKM Dengan Motivasi Berwirausaha Sebagai Pemediasi (Studi pada UMKM Pendatang dan asli NTT di Kota Kupang) - Stefanie Noviega Bribin Burin; Maria Augustin Lopes Amaral; Adrianus Jou Sewa (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2023)
The existence of this study aims to determine how much influence cultural values have on the performance of MSMEs, both from East Nusa Tenggara (NTT) and migrants from outside NTT with entrepreneurial motivation as mediators. The sample in this study was 170 which were divided into two for native MSMEs and immigrants from outside NTT. All data collected using SEM-PLS analysis technique with Smart PLS 3.0. The results of this study indicate there is a positive influence between motivation and performance for MSMEs native to NTT and immigrants. Cultural values have no effect on performance in both. There is a positif influence between Cultural values and motivation, and motivation mediates the influence of cultural values on performance both in MSMEs native to NTT and immigrants from outside NTT.